Pro-poor intervention strategies in irrigated agriculture in Asia: poverty in irrigated agriculture: issues and options: Bangladesh - Ahmad, Q.K.; Karim, Zahurul; Haq, Azharul; Quasem, Abdul; Hussain, Intizar; Rahman, K.; Chakravorty, N.; Ali, Noajesh; Akhter, Rowshan; Hasan, Zubair; Younus, A.F.; Hossain, Afzal; et al. (International Water Management Institute, 2004)
IWMI-ADB Project